Mapping of Design Rainfall at Multiple Return Periods Using Spatial Interpolation in Abab Sub-Watershed, Blitar Regency - Ageng Galih Fans Muhammad Fiqri; Donny Harisuseno; Jadfan Sidqi Fidari (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
The main occupation of residents who live in Abab Sub-Watershed, Blitar Regency, is as farmers in agriculture and plantations. Agriculture and plantations need rain data that have been calculated to maximize the yields to be obtained. Hydrometeorological disasters, specifically floods, often occur at this location. Therefore, research is needed on calculating design rainfall, outlined in easy-to-understand isohyet maps. The research aims to assist the planning of water structures or other hydrological research without having to recalculate or retest data from the beginning. This study's utilized return periods were 2, 5, 10, and 25 years, plotted as isohyet maps. Before calculating the design rainfall, the rainfall data had to be tested first. Calculation of design rainfall used SMADA Distrib 2.13 application and was tested with the distribution suitability test. The results of the distribution suitability test showed that Log Normal is appropriate to be used. The results of plotting the design rainfall on an isohyet map using the IDW, Kriging, and Spline methods showed that the IDW and Spline maps are smoother and not as broken as Kriging. Next, a comparative analysis of RMSE and NSE was carried out. For return periods of 2, 5, 10, and 25 years, IDW has the smallest RMSE mean value of 0.016 and the highest NSE average value of 0.9999.